The Effects of Brief Mindfulness Training on Attentional Processes: Mindfulness Increases Prepulse Facilitation but Not Prepulse Inhibition - Åsli, Ole; Johansen, Marta F.; Solhaug, Ida (Frontiers in Psychology, 2021)
Mindfulness is intentional focus of one's attention on emotions, thoughts or sensations occurring in the present moment with a nonjudgmental attitude. Recently there has been increased interest in the effects of mindfulness practice on psychological processes such as concentration, focus and attention. In the present study, a prepulse inhibition/facilitation (PPI/PPF) paradigm was employed to investigate the effect of brief mindfulness practice on automatic attention regulation processes. PPI occurs when a relatively weak prepulse (e.g. a tone) is presented 30-500 ms before a startle-inducing stimulus, and reduces the magnitude of the startle response. Prepulse facilitation (PPF) is the increase in startle magnitude when the prepulse is presented 500 ms or more before the startle-eliciting stimulus. In the present study, the effect of engaging in a 23-min mindfulness exercise on PPI and PPF was investigated. Participants listened to either a mindfulness instruction (mindfulness group) or relaxing music (control group). In a PPI/PPF pre- and posttest, a startle-eliciting noise was presented at lead intervals of 60, 120 and 2000 ms. Results showed that engaging in brief mindfulness practice increased prepulse facilitation at the 2000 ms lead interval in the posttest compared to the pretest. The amount of PPI did not differ between tests.